Odpowiedzi

2010-03-21T21:42:07+01:00
Mg+h2co3 powst MGCO3 + H2
MgO + h2co3 = MGCO3 + h2o
Mg(OH)2 + h2co3= MGCO3 + 2h2o

6K + 2H3PO4 = 2K3po4 + 3h2
3K2O + 2H3PO4 =2K3po4 + 3H2O
3KOH + H3PO4= K3po4 + 3H2O
2010-03-21T21:44:11+01:00
Odpowiedź w załączniku

Pozdrawiam ;-DDD
Najlepsza Odpowiedź!
2010-03-21T21:47:49+01:00
MgCO3 i K3PO4

1) MgO + H2CO3 => MgCO3 + H2O
2) Mg + H2CO3 => MgCO3 + H2
3) Mg(OH)2 + H2CO3 => MgCO3 + 2H2O

1)6K + 2H3PO4 => 2K3PO4 + 3H2
2)3K2O + 2H3PO4 => 2K3PO4 +3H2O
3) 3KOH + H3PO4 => K3PO4 + 3H2O